Depression in primary care and the role of evidence-based guidelines: cross-sectional data from primary care physicians in Germany - Sonia Lech; Wolfram Herrmann; Sebastian Trautmann; Ulrich Schwantes; Paul Gellert; Joachim Behr; Pichit Buspavanich (BMC, 2022)
Abstract Background Depression is the most common mental health burden worldwide. Primary care physicians (PCPs) play a key role in the care provision for people with depression. The first objective of the present study was to examine the health care situation of depression in primary care, focusing on the cooperation between PCPs and mental health specialists. Secondly, we aimed at examining the role of the German S3 Guideline for Unipolar Depression in the primary care provision. Methods Data of N = 75 PCPs were analysed from a cross-sectional online survey. Analysis of descriptive information on the current status of primary health care and depression was conducted. Further, to examine factors that are related to the usage of guidelines, multiple regression was performed. Results Only 22.1% of PCPs described the quality of cooperation with ambulatory mental health specialist as good. The most frequent problems in the cooperation were of structural nature (49.3%, long waiting list, few therapy units, as well as barriers in the communication and the information exchange). With regard to the role of the guideline, 65% of PCPs reported never or seldom using the guideline and 31.7% of PCPs perceived the guideline as not useful at all. In addition, perceived usefulness of the S3 guideline was positively associated with the usage of the guideline. Results of the logistic regression revealed a significant association between the usage of the German S3 Guideline for Unipolar Depression and rating of perceived usefulness of the guideline (OR: 4.771; 95% CI: 2.15-10.59; p < 0.001). Conclusion This study highlights the central role of PCPs and demonstrates major barriers in the outpatient health care provision of depression. Present findings suggest a strong need for collaborative health care models to resolve obstacles resulting from fragmented mental health care systems. Finally, reported perceived barriers in the implementation of the German S3 Guideline for Unipolar Depression indicate the urge to involve PCPs in the development of evidence-based guidelines, in order to ensure a successful implementation and usage of guidelines in clinical practice.